2018
DOI: 10.1111/bjd.16905
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of the amino acid transporters SLC 7A5, SLC 7A7, SLC 7A8 and the enzyme TDO 2 in basal cell carcinoma

Abstract: This study highlights the upregulation of SLC7A5, SLC7A8 and TDO2 in BCC compared with nontumour skin. Our findings imply that amino acid transporters may be further explored as potential targets for future medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Obtained data revealed that in rectal cancer samples the kynurenine pathway was characterized by TDO2 overexpression, while IDO1 expression remained practically unchanged (using a 1.5-fold ratio criterion). These data are consistent with others reported in literature, in which TDO2 expression in several human tumor cell lines and tissues has been demonstrated ( 26 , 28 , 40 42 ). Similarly, a rise in the calculated enzymatic activity (KYN/TRP * 1,000) in rectal cancer tissues compared to mucosa was detected (mean activity: 111 and 230 for healthy mucosa and rectal cancer, respectively; p < 0.05, Wilcoxon signed-rank test).…”
Section: Resultssupporting
confidence: 94%
“…Obtained data revealed that in rectal cancer samples the kynurenine pathway was characterized by TDO2 overexpression, while IDO1 expression remained practically unchanged (using a 1.5-fold ratio criterion). These data are consistent with others reported in literature, in which TDO2 expression in several human tumor cell lines and tissues has been demonstrated ( 26 , 28 , 40 42 ). Similarly, a rise in the calculated enzymatic activity (KYN/TRP * 1,000) in rectal cancer tissues compared to mucosa was detected (mean activity: 111 and 230 for healthy mucosa and rectal cancer, respectively; p < 0.05, Wilcoxon signed-rank test).…”
Section: Resultssupporting
confidence: 94%
“… 64 , 73 Specifically, TDO2 has been reported to be expressed in malignant glioma, hepatic carcinoma, non-small cell lung carcinoma (NSCLC), RCC, ovarian carcinoma, breast cancer, bladder cancer, basal cell carcinoma and melanoma. 7 , 15 , 74 76 In co-cultures of glioblastoma cells with mixed leucocyte reactions (as an assay of T-cell competence), tumour cell TDO2 expression suppressed T-cell proliferation via the production of Kyn. 7 This immunosuppressive effect was also observed in vivo, as TDO2 expression inhibited immune infiltration into gliomas 7 and prevented tumour rejection in immunised mice.…”
Section: Trp-catabolising Enzymes (Tce)mentioning
confidence: 99%
“…From a medical point of view, LAT2 is expressed in several tissues as the brain, heart, small intestine, lung, spleen, liver, prostate, kidney, ovary, testis, skeletal muscle, placenta, and fetal liver [ 1 ]. Whereas the loss of LAT2-dependent transport function is attributed to age-related hearing loss, renal aminoaciduria, and cataract formation [ 1 , 13 , 14 , 15 ], an elevated expression level of LAT2 is linked to cancer [ 16 ].…”
Section: Introductionmentioning
confidence: 99%